Identification of clinically-informative biomarkers within the spectrum of gastro-oesophageal reflux disease in the South African population - Van Rensburg, C. J. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD (Pathology. Anatomical Pathology))--University of Stellenbosch, 2006.